The Synchronization Transceiver Design and Experimental Verification for the LuTan-1 SAR Satellite - Yuanbo Jiao; Da Liang; Kaiyu Liu; Yafeng Chen; Huaizu Wang; Robert Wang (Sensors, 2020)
The deviation between the two oscillators in BiSAR systems will cause a residual modulation of echo signal. Therefore, the phase synchronization is an important issue that must be addressed for BiSAR systems. An advanced non-interrupted phase synchronization scheme is used for the LuTan-1 SAR satellite. The synchronization transceiver (STR) is designed for transmitting and receiving synchronization signals. In addition, STR mainly consists of master and auxiliary transceivers and switch module. Furthermore, the function and working principle of STR are introduced, and the detailed design of each part is described. The measured results are also evaluated to prove the performance of the STR. In addition, the phase synchronization accuracy is also demonstrated to verify the effectiveness of the non-interrupted synchronization scheme. The standard deviation (STD) of the residual phase is less than 0.3 degrees. The results have guiding significance for the synchronization unit design of LuTan-1 and the future BiSAR system.